Impact of planted hedgerow fallows on nutrient balances in a groundnut/maize/cassava intercrop. Issue 3 (23rd February 2020) - Hauser, Stefan
ABSTRACT: To assess if the nutrient supply through planted tree fallows meets crop nutrient uptake and export, N, P, K, Ca and Mg uptake and export by a groundnut/maize/cassava intercrop was compared with the nutrient uptake by three planted fallow systems ( Senna spectabilis, Flemingia macrophylla, Dactyladenia barteri ) and a no-tree control. Three cycles of two years fallow and one year cropping on Ultisol in southern Cameroon were studied. Fallows were slashed and burned. The fallow system had no consistent effect on nutrient uptake by individual crops. Crop nutrient uptake was most often highest in the S. spectabilis system. Nitrogen balances were generally negative due to N loss in the burn. Across three cropping cycles, the balance of fallow nutrient uptake versus total crop nutrient uptake was only in the S. spectabilis system positive for all nutrients. Nutrient export by all crops (mean of three years) was unaffected by fallow systems. The fallow nutrient uptake versus crop nutrient export balance was positive for all nutrients and systems. Planted fallows appear capable of acquiring sufficient nutrient stocks during fallow phases, covering the crops' demand. Fallow N and K uptake and crop export declined with every fallow/cropping cycle.